Trojan Horse Protest at Pashayan/Stockman Dinner At Fresno Hilton Hotel - Watkins, Howard::::::::: (1982)
Protesters carrying signs by giant Trojan Horse: Ellen Jahn in blue shorts, George Ballis in brown shirt